Support Needs for Canadian Health Providers Responding to Disaster: New Insights from a Grounded Theory Approach - Fahim, Christine (PLoS Curr, 2015)
Introduction: An earlier descriptive study exploring the various supports available to Canadian health and social service providers who deployed to the 2010 earthquake disaster in Haiti, indicated that when systems are compromised, professionals are at physical, emotional and mental risk during overseas deployment. While these risks are generally well-identified, there is little literature that explores the effectiveness of the supports in place to mitigate this risk. This study provides evidence to inform policy development regarding future disaster relief, and the effectiveness of supports available to responders assisting with international disaster response. Methods: This study follows Strauss and Corbin’s 1990 structured approach to grounded theory to develop a framework for effective disaster support systems. N=21 interviews with Canadian health and social service providers, who deployed to Haiti in response to the 2010 earthquake, were conducted and analyzed. Resulting data were transcribed, coded and analysed for emergent themes. Results and Discussion: Three themes were identified in the data and were used to develop the evolving theory. The interview data indicate that the experiences of responders are determined based on an interaction between the individual’s ‘lens’ or personal expectations, as well as the supports that an organization is able to provide. Therefore, organizations should consider the following factors: experience, expectations, and supports, to tailor a successful support initiative that caters to the needs of the volunteer workforce.